Prediction of stiffness from orientation data of glass reinforced injection moldings - Neves, N. M. (1999)
The complex thermo-mechanical process developing in injection molding leads to through-thickness and point to point variation of fiber orientation. It is not economically viable to characterize experimentally the variation of fiber orientation. Thus, efforts have been put into modeling the fiber orientation in injection molding. Some commercially available programs already allow the prediction of fiber orientation distribution in moldings. If the fiber orientation field is known it is possible to calculate the major elastic properties, which can be input into finite-element structural analysis codes to predict product performance. That approach was followed in this work to compare the experimental flexure behavior of glass fiber reinforced polycarbonate injection molded discs with predictions obtained from FEM simulations. The data used in the FEM code was calculated from the fiber orientation data predicted using the software C-Mold.